1968
DOI: 10.1139/p68-555
|View full text |Cite
|
Sign up to set email alerts
|

The D and D′ states of the PO molecule

Abstract: A rotational analysis of the 0–0, 0–1, and 0–2 bands of the D–B and D′–B systems of PO in the region 5500–6900 Å has been carried out from a spectrum obtained at a resolution higher than that of previous workers (Couet and Guenebaut 1966; Couet et al. 1967). The mutual perturbation between D2Πr and D′2Πr has been confirmed from the rotational analysis of the 0–0 and 0–1 bands of the D–A and D′–X systems in the region 2000–2200 Å. The analysis of the D′–X bands has shown that the previously reported E′ state ly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

1970
1970
2011
2011

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…These constants give AGlI2 = 1220.18 cm-I in exact agreement with the value recently established by Verma and Dixit (1968). The vibrational constants of X211 established from the present work are in agreement with those given by Rao from a rotational analysis of they bands.…”
Section: Experimental Procedures and Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…These constants give AGlI2 = 1220.18 cm-I in exact agreement with the value recently established by Verma and Dixit (1968). The vibrational constants of X211 established from the present work are in agreement with those given by Rao from a rotational analysis of they bands.…”
Section: Experimental Procedures and Resultssupporting
confidence: 92%
“…Experimental conditions and the spectrograph used in photographing the spectrum were the same as described recently by Verma and Dixit (1968). The new spectrum was excited by an r.f.…”
Section: Experimental Procedures and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…glow are B' 211i-X 'I1, (Verma 1970), C' 2Z-X 211r (Narasimham et al 1965 ;Guenebaut et al 1966), C-X211, (Dressler 1955), and D 211,-X211, (Dressler 1955 ;Verma and Dixit 1968). Bands belonging to the B1-X transition are superimposed on the continuum in the region 3800-4500 A. Wavelengths (A) and assignments of the new B'-X bands are 4444.7 (0-9), 4345.6 (1-9), 4300.5 (1-9), 4208.4 (2-9), and 4167.2 (2-9).…”
mentioning
confidence: 99%
“…In a recent paper (Verma and Dixit 1968) it was shown that the rotational structure of the D' state breaks off at 49 536 cm-' above X211 (To = 0). No other level of D and D', above 49 536 cm-' has been observed.…”
Section: E Dissociation Energy and Predissociationmentioning
confidence: 98%